MAKNA DAN FUNGSI UNGKAPAN METAFORIS DALAM WACANA HUKUM PADA SURAT KABAR HARIAN JAWA POS - Sukarno, Sukarno (Jurnal Pendidikan Bahasa dan Sastra, 2017)
This research aims to describe the semantic components of the metaphorical expressions found in the law discourse of the Jawa Pos daily newspaper by contrastingÂ  the semantic components of the source domain (the literal expressions) and the target domain (the metaphorical expressions) to discover the similarities of meanings of, and to reveal the functions of the metaphorical expressions used in the discourse. The data were collected using non-participatory observation, critical reading, and note-taking. The data were analyzed using referential identity and distributional methods with substitution and paraphrasing techniques. The result of the research reveals two main findings. First,the association of the source and the target domains can be elaborated by analyzing the diagnostic components of each domain. The analysis uncovers four similarities of meanings: in action, qualities, movement, and attributes. Secondly, the metaphorical expressions in this discourse are mainly used for popularizing or dramatizing the issue to draw the readersâ€™ attention to increase the sale of the newspaper, and to criticize and denigrate the law executers (prosecutors and judges) to be more objective in doing their jobs so that law enforcement in Indonesia will be more powerful.Keywords : metaphorical expressions, semantic components, source,target, meanings, functions